2018
DOI: 10.1111/cge.13451
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Phelan‐McDermid syndrome: The impact of the PNPLA3 p.I148M polymorphism

Abstract: The PNPLA3 gene maps in the 22q13 region and can have modifying effects on the phenotype of patients with Phelan‐McDermid syndrome (PMS). The PNPLA3 p.I148M variant was detected in two PMS patients presenting with refractory seizures, gastrointestinal issues, and liver dysfunction. The p.I148M variant leads to macrovescicular steaosis and predisposes to liver disorders from steatohepatitis to fibrosis. Accumulation of lipid macrovescicles in the hepatocytes affects several pathways, including the metabolismof … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…PNPLA3 has been associated with liver dysfunction in two individuals with PMS. 47 SULT4A1 is speculated to be part of a contiguous gene syndrome proximal to small 22q13 deletions within the PMS population. 10 Our hypothesis for this study was that SHANK3 may not be the only gene involved in the pathogenesis of seizures in PMS, as has been noted in the literature related to SHANK3 mutations in mice as well.…”
Section: Genetic Associationsmentioning
confidence: 99%
“…PNPLA3 has been associated with liver dysfunction in two individuals with PMS. 47 SULT4A1 is speculated to be part of a contiguous gene syndrome proximal to small 22q13 deletions within the PMS population. 10 Our hypothesis for this study was that SHANK3 may not be the only gene involved in the pathogenesis of seizures in PMS, as has been noted in the literature related to SHANK3 mutations in mice as well.…”
Section: Genetic Associationsmentioning
confidence: 99%
“…Some studies have identified specific genes within the commonly deleted 22q13.3 region as potential contributors to the PMS phenotypes [26,27], suggesting, among the others, a role for the SULT4A1 gene in speech delay and abnormal cerebellar development and function, BRD1 in neuropsychiatric disorders [28], and GRAMD4, SCO2, and TYMP in mitochondrial abnormalities [29]. Moreover, the loss of one allele of the PNPLA3 gene due to a large 22q13.3 deletion can unmask a heterozygous variant, increasing the risk of liver disease, leading to gastrointestinal issues and abnormal responses to various drugs [30].…”
Section: Pathogenic Molecular Mechanisms In Pmsmentioning
confidence: 99%
“…Clinical features are summarized in Table 3 with details following. Clinical traits for patients 2 and 5 were described in detail in a previous study [35] and only the most relevant features are reported herein. PMS 1.…”
Section: Clinical Features Of Selected Individuals With Pmsmentioning
confidence: 99%